Influencia de la ceniza de caña, aditivo superplastificante y tiempo de curado sobre la compresión, rigidez, capacidad de llenado - paso y fluidez de un concreto autocompactante - Mego Zapata, Juan Carlos (2018)
The present project is focused on improving the mechanical and rheological properties of a self-compacting concrete (CAC) made with the addition of cane leaf ash as a pozzolanic material and superplasticizer additive to maintain workability. Generating the option of manufacturing industrial waste from burning cane leaf during harvest, which represents one of the largest environmental pollutants in northern Peru. The design of the mixture was based on the recommendations stipulated by the committee ACI - 211 (American Concrete Institute), modifying the additive dose for each percentage of addition of pozzolan to achieve the parameters of its capacity of filling and fluidity stipulated by the American Society of Testing Materials (ASTM C1611), passing capacity (ASTM C1621) and specifications of the European Federation of Specialist Construction Chemicals and Concrete Systems (EFNARC, 2002) and the European Project Group (GPE, 2005) We determined that the self-compacting concrete with addition to 2.5% ash and 1.18% superplasticizer additive satisfactorily meets all the requirements for a self-compacting concrete, reaching an extension of 760 mm, with a flow time of 9.90 seconds, without blocking tendency, achieving a compressive strength of 567 kg / cm2 (11% increase with respect to the standard specimen) with a stiffness of 317,962.55 kg / cm2 (12% increase with respect to the standard specimen) at 56 days of curing. Results with the sample of addition of ash to 3.0% on the concrete mixture, achieved a compressive strength of 597 kg / cm2 (17% increase with respect to the test specimen) and a rigidity of 322,306.51 kg / cm2 (13 % increase with respect to the test specimen) to 56 days of curing. The evaluation of the rheological properties of the concrete determined that the samples up to 2.5% of ash addition improve their self-compacting properties by increasing the filling capacity, fluidity and capacity of passage without the presence of segregation, except for the 3.0% sample that presents a low fluidity and the sample at 3.5% ash, which, in addition to low fluidity, also has a limited flow capacity.